Evaluation of the Functional and Radiological Outcomes of Fixed Angle versus Variable Angle Volar Locking Compression Plates in Managing Intra-articular Fractures of Distal End Radius - Garg DK; Sakale H; Agrawal AC; Kar B; Pandiyarajan E; Yadav SK (Malaysian Orthopaedic Journal)
Introduction: Distal end radius fractures are common upper extremity fractures often requiring surgical intervention for instability. This study compares the functional and radiological outcomes of fixed angle versus variable angle volar locking compression plates in managing these fractures. Materials and methods: A prospective randomized study was conducted at AIIMS, Raipur, from July 2020 to December 2022. Patients aged 18-60 years with complete intra-articular distal end radius fractures (AO Type 23C1, 23C2, 23C3) were included. Sixty-four patients were randomized into two groups: one receiving fixed angle plates (Group 1) and the other variable angle plates (Group 2). Functional outcomes were assessed using the Mayo wrist score, and radiological outcomes were evaluated with the Sarmiento modification of Lindstrom’s criteria. Statistical analysis was performed using IBM SPSS 22.0, with p-values <0.05 considered significant. Results: At 3 months, the variable angle group had significantly higher Mayo wrist scores (63.12 ± 11.81) compared to the fixed angle group (48.75 ± 11.90, p=0.005). This trend continued at 6 months (75.93 ± 9.16 vs. 64.37 ± 14.59, p=0.025) and 1 year (91.87 ± 7.27 vs. 81.25 ± 16.17, p=0.044). Radiologically, the variable angle group demonstrated better volar tilt restoration at all follow-up points (p<0.001 at 3 months, p=0.001 at 6 months, p=0.004 at 1 year). Complication rates were similar between groups. Conclusion: Variable angle volar locking compression plates offer superior functional outcomes and better volar tilt restoration compared to fixed angle plates for unstable distal end radius fractures. Both types exhibited similar complication rates.